Fibrinogen and fibrin: An illustrated review - Pieters, Marlien; Wolberg, Alisa S. (Research and practice in thrombosis and haemostasis, 2019)
Since its discovery over 350 years ago, studies of fibrinogen have revealed remarkable characteristics. Its complex structure as a large (340 kDa) hexameric homodimer supports complex roles in hemostasis and homeostasis. Fibrinogen synthesis is regulated at the transcriptional and translational levels, undergoing both constitutive (basal) secretion from liver, and inducible upregulation in response to inflammatory events. In addition, alternative splicing yields fibrinogen variants with unique properties and contributions to coagulation biochemistry. During coagulation, fibrinogen conversion to fibrin occurs via thrombin‐mediated proteolytic cleavage that produces intermediate protofibrils and then mature fibers that provide remarkable biochemical and mechanical stability to clots. Fibrin formation, structure, and stability are regulated by various genetic, biochemical, and environmental factors, allowing for dynamic kinetics of fibrin formation and structure. Interactions between fibrinogen and/or fibrin and plasma proteins and receptors on platelets, leukocytes, endothelial cells, and other cells enable complex functions in hemostasis, thrombosis, pregnancy, inflammation, infection, cancer, and other pathologies. Disorders in fibrinogen concentration and/or function increase risk of bleeding, thrombosis, and infection. This illustrated review covers fundamental aspects of fibrinogen and fibrin biology, biochemistry, biophysics, epidemiology, and clinical applications. Continued efforts to enhance our understanding of fibrinogen and fibrin in these processes are likely to advance treatment and prevention of many human diseases.